Single-image reflectance estimation for relighting by iterative soft grouping - Li, Yuanzhen; Lin, Steve; Kang, Sing Bing; Lu, Hanqing; Shum, Harry (Pacific Conference on Computer Graphics and Applications (PG), 2002)
Reflectance values for image-based relighting are often estimated from grouped pixels with similar reflectance, but such groupings are difficult to compute with certainty for sparse image data. To address this problem, we propose an iterative method that aggregates BRDF data in a single image with known geometry and lighting by soft grouping, where pixels contribute to one another's estimate according to their degree of reflectance similarity. Estimation of specular reflectance is further improved by albedo-independent soft grouping of pixels based on shape continuity. With recovered reflectances, we demonstrate realistic relighting for synthetic and real scenes, including surfaces with spatially-varying reflectance.